Photovoltaic pumping system control based on DC motor - YOUMBAI FATMA ZOHRA; YOUMBAI MOHAMMED LAID (University of Shahid Hama Lakhdar - El Oued, 2025)
This thesis focuses on the modeling and control of a photovoltaic water pumping system using a separately excited DC motor. The main objective was to enhance system efficiency through Maximum Power Point Tracking (MPPT) techniques, specifically Perturb & Observe (P&O) and Incremental Conductance (INC) algorithms. A detailed simulation model was developed using MATLAB/Simulink to assess the system’s performance under variable irradiance conditions. The results demonstrated that the INC algorithm achieved faster convergence and higher tracking accuracy compared to P&O, making it more suitable for dynamic environments. في ھذه المذكرة، تم دراسة وتصمیم نظام ضخ كھروضوئي یعتمد على محرك تیار مستمر . تم التركیز على تحسین كفاءة النظام باستخدام تقنیات تتبع نقطة القدرة العظمى (MPPT) ، حیث تم تنفیذ خوارزمیتي (P&O) Observe & Perturb ، MATLAB/Simulinkبرنامج باستخدام متكامل محاكاة نموذج بناء تم Incremental Conductance (INC). و وتم تحلیل الأداء تحت ظروف إشعاعیة متغیرة . أظھرت النتائج أن خوارزمیة INC توفر دقة واستجابة أسرع مقارنة ب P&O ، مما یجعلھا أكثر ملاءمة للأنظمة الدینامیكیة
Master's theses: specializing Electrical control
Keywords: pump; solar energy; direct current; مضخة ، طاقة شمسیة ، تیار مستمر